Influence of indoor formaldehyde pollution on respiratory system health in the urban area of Shenyang, China - Zhai, L (Makerere Medical School, 2013)
BACKGROUND: The decoration of interior spaces can lead to dangerous levels of indoor formaldehyde pollution. Exposure to indoor air pollution may be responsible for nearly 2 million deaths per year in developing countries. OBJECTIVES: To assess the prevalence of indoor formaldehyde pollution caused by decoration and resultant respiratory system symptoms exhibited in exposed adults and children, due to indoor formaldehyde pollution caused by decoration. METHODS: Survey sites were chosen and indoor formaldehyde concentrations determined according to the standard of formaldehyde in GB50325-2001. Logistic regression models were used to derive odds ratios (ORs) and 95% confidence intervals (95% CIs) after adjusting for potential confounders for this survey. RESULTS: Formaldehyde concentration was above the standard in 64% of Shenyang City. Some adults surveyed complained of common respiratory system disorders, including coughing (11.8%), nasal irritation (39.2%), Heterosmia (14.51%), and throat irritation (25.27%); 12% of children suffered from asthma. The analysis identified formaldehyde pollution and ventilation frequency as risk factors for respiratory system disorders in both adults (OR=2.603, [95% CI: 1.770–3.828], OR=1.604, [95% CI: 1.146–2.244], respectively) and children (OR=4.250, [2.064–8.753], OR=1.831, [1.006–3.333], respectively). CONCLUSION: The prevalence of common respiratory system disorders was related both to formaldehyde pollution and insufficient ventilation after decorating.